The anti-sigma factor RsrA responds to oxidative stress by reburying its hydrophobic core - Rajasekar, K; Zdanowski, K; Yan, J; Hopper, J; Francis, M; Seepersad, C; Sharp, C; Pecqueur, L; Werner, J; Robinson, C; Mohammed, S; Potts, J; et al. (Nature Publishing Group: Nature Communications, 2016)
Redox regulated effector systems that counteract oxidative stress are essential for all forms of life. Here, we uncover a new paradigm for sensing oxidative stress centred on the hydrophobic core of a sensor protein. RsrA is an archetypal zinc-binding anti-sigma factor that responds to disulfide stress in the cytoplasm of Actinobacteria. We show that RsrA utilizes its hydrophobic core to bind the sigma factor σR preventing its association with RNA polymerase, and that zinc plays a central role in maintaining this high-affinity complex. Oxidation of RsrA is limited by the rate of zinc release, which weakens the RsrA-σR complex by accelerating its dissociation. The subsequent trigger disulfide, formed between specific combinations of RsrA’s three zinc-binding cysteines, precipitates structural collapse to a compact state where all σR-binding residues are sequestered back into its hydrophobic core, releasing σR to activate transcription of anti-oxidant genes.